HUBUNGAN ANEMIA DALAM KEHAMILAN DENGAN PERDARAHAN POSTPARTUM KARENA ATONIA UTERI DI RSUD SYAMRABU BANGKALAN - Semi; Niah, Najah Soraya; Fatmawati, Istiadah; Khotimah, Husnul (PRIMA WIYATA HEALTH, 2025)
Background: Anemia is a micronutrient problem that occurs widely worldwide, especially in developing countries, which is estimated to occur in 30% of the world's population. Postpartum hemorrhage is bleeding that is more than 500 cc that occurs after the baby is born vaginally or more than 1000 mL after an abdominal delivery. Objectives: The study's purpose is to determine whether there is a relationship between anemia in pregnancy and postpartum bleeding due to uterine atonia. Methods: The research design used cross-sectional. The population was all pregnant women with postpartum hemorrhage due to uterine atonia as many as 34 respondents, the sample was pregnant women with postpartum hemorrhage due to uterine atonia as many as 34 respondents, with a total sampling technique. The independent variable was anemia in pregnancy and the dependent variable was uterine atonia, data collection techniques using questionnaires, and data processing by editing, coding, scoring, and tabulating. Data analysis using the Chi-square test. Results: Data analysis using the Chi-square test can be found from 34 mothers giving birth at Syamrabu Bangkalan Hospital, 11 mothers with anemia in pregnancy were obtained, 45.5% experienced postpartum bleeding due to uterine atonia and 54.5% did not bleed. Meanwhile, 23 mothers did not experience anemia in pregnancy with 4.3% experiencing postpartum hemorrhage due to uterine atonia and 95.7% not experiencing postpartum hemorrhage. The results of the statistical test using there is a relationship between anemia in pregnancy and postpartum bleeding because of uterine atonia using the statistical p-value of the Chi-square p-value test < 0.05, then there is a relationship between the two variables with a p-value of 0.001 < 0.05.   Conclusion: It can be concluded that there is a relationship between anemia in pregnancy and postpartum bleeding due to uterine atonia.